A review on fermentative hydrogen production from dairy industry wastewater. Issue 11 (13th August 2014) - Karadag, Dogan; Köroğlu, Oguz Emre; Ozkaya, Bestami; Cakmakci, Mehmet; Heaven, Sonia; Banks, Charles
Abstract Hydrogen (H2) is one of the most promising alternative fuel sources for satisfying future energy demand, and fermentative hydrogen production is advantageous over other processes. In recent decades, considerable research has been conducted on H2 production from carbohydrate‐rich materials since it is a cost‐effective approach and has the ability to generate intensive renewable energy from organic wastes. Dairy wastewater is a high volume industrial wastewater and with its immense carbohydrate content is an attractive candidate for sustainable fermentative H2 production. The present paper provides comprehensive evaluation of recent reports on fermentative H2 production from dairy wastewater. Important effective parameters and current bioreactor technologies for H2 production from dairy wastewater are discussed. © 2014 Society of Chemical Industry